Budaya organisasi dan kode etik pustakawan dalam implementasinya - Panti Panti (UIN Sumatera Utara, 2015)
Librarians actually played a major role in contributing to the development of a civilized. but its role is not seen by most people . The problem is when people seeing the library, as if the librarian is blocked by a row of collection that is increasingly to be older and increasingly away from the elements to present . That said, when mentioning the word library, people thinks refer to a medium of human civilization, namely books. For a long time, the book became the primary knowledge resource, compiled by the library. This happens because the position of the library was considered only as a storage place only, and turns up the assumption that the modern age so shall still can not be eliminated. Judging by the cases me